INTERNATIONAL COMPETITIVENESS OF COUNTRIES – EVIDENCE FOR SOME DEVELOPED AND EMERGING ECONOMIES - Herciu, Mihaela; Ogrean, Claudia (European Scientific Journal, ESJ, 2013)
This paper identifies and analyzes the international competitiveness of some national economies (developed and developing) by emphasizing similarities and differences between the countries regarding the competitive advantages, on one hand, and the problematic factors for business environment, on the other hand and. The experiences of the 11 analyzed countries by this paper (United States, United Kingdom, Germany, France, Japan, Brazil, China, India, Russia, Chile, Mexico) are able to outline some direction that some countries, especially Romania, must follow in order to obtain or increase international competitiveness.